Clinical and epidemiological aspects of yersinioses in Kharkiv region - Mohylenets, O (Annals of Mechnikov's Institute, 2020)
Despite great success in diagnostics of infectious diseases and development of new laboratory methods, vast majority of cases are not diagnosed or registered as different diagnosis. It connected with polymorphism of clinical signs and difficulty of specific diagnostics. The most evidential method of diagnostics is culture, but grows of Yersinia spp. on common media is very bad. More specific and modern methods are immunoferment analysis (IFA), polymerase chain reaction, immunoblot analysis, but this methods are rather expensive and require specialized laboratory equipmet and staff. Indirect hemahlutination test (IHAT) is still more common in Ukraine. Materials and methods The object of the study were 61 patients with yersiniosis who were treated in the Kharkiv Regional Clinical Infectious Diseases Hospital during five years. The diagnosis of yersiniosis in all patients was based on epidemiological, clinical, anamnestic data; results of additional laboratory studies which were in accordance with generally accepted clinical criteria. Final diagnosis was confirmed by results of serological studies (IHAT in pair serum with Yersinia enterocolitica 03, Yersinia enterocolitica 09 and Yersinia pseudotuberculosis antigen). For exclusion of viral hepatitis patients with jaundice were checked for anti-HAV IgM, HbsAg, and anti-HCV ІgG by IFA. Statistical data processing was carried out by means of Statistica 6,0 software package. Comparative group analysis was perfomed by using χ2 (Pearson) criterium. Differences with p<0,05 were considered statistically significant. Results and Discussion From the 61 patients that were under our supervision, in 59 was diagnosed intestinal yersiniosis, in 2 – pseudotuberculosis. Patients up to 50 years old were dominated. The incidence was recorded throughout the year in the form of sporadic cases. The severity of the disease in most cases was moderate (55,7%) or mild (32,8%). Severe disease was registered in 7 patients. Generalized (46%) and gastrointestinal (42%) forms dominated. Most patients – 39 (64%) – experienced acute onset of the disease. Climax period was characterized by considerable polymorphism. Intoxication syndrome was predominant. Catarrhal, gastrointestinal and abdominal syndromes, hepatomegaly, polylymphadenopathy and rash were observed often enough. Arthralgic syndrome, splenomegaly, kidney affection were revealed less frequently. Conclusions 1. In the Kharkiv region intestinal yersiniosis prevailed above pseudotuberculosis. The main causative agent is Y.enteroccolitica O3. 2. Disease was registered as sporadic cases, that occured throughout the year. Male persones of working age were mainly affected. 3. The clinic of yersiniosis was characterized by pronounced polymorphism, which lead to difficulties in diagnosis. About half of patients had signs of process generalization. 4. Specific laboratory methods, including IFA and PCR (as addition to stool culture and IHAT), should be prescribed to reveal real situation about incidence of disease, improve the diagnostics and further treatment.